Forensic science in the Global South: addressing Brazilian fingerprint experts’ challenges - Lopes, Thais; Sauzier, Georgina; Barros, R.M.; Lewis, Simon W. (Taylor & Francis, 2024)
Brazil is the world’s fifth largest country by land mass and seventh most populous. It presents a wide range of geographical and environmental differences in addition to heterogeneous resource availability, leading to major challenges in forensic science service provision. Here, we report the initial results from a survey of Brazilian fingerprint practitioners conducted in early 2023 to better comprehend the tools used for the recovery and detection of latent fingermarks, and to identify the main challenges facing Brazilian fingerprint practitioners in this regard. This will subsequently form the basis for the targeted development of sustainable latent fingermark protocols suitable for deployment in the Brazilian context.